Anti-Inflammatory and Antinociceptive Activities of Anthraquinone-2-Carboxylic Acid. (3rd January 2016) - Park, Jae Gwang; Kim, Seung Cheol; Kim, Yun Hwan; Yang, Woo Seok; Kim, Yong; Hong, Sungyoul; Kim, Kyung-Hee; Yoo, Byong Chul; Kim, Shi Hyung; Kim, Jong-Hoon; Cho, Jae Youl
Abstract : Anthraquinone compounds are one of the abundant polyphenols found in fruits, vegetables, and herbs. However, the in vivo anti-inflammatory activity and molecular mechanisms of anthraquinones have not been fully elucidated. We investigated the activity of anthraquinones using acute inflammatory and nociceptive experimental conditions. Anthraquinone-2-carboxylic acid (9, 10-dihydro-9, 10-dioxo-2-anthracenecarboxylic acid, AQCA), one of the major anthraquinones identified from Brazilian taheebo, ameliorated various inflammatory and algesic symptoms in EtOH/HCl- and acetylsalicylic acid- (ASA-) induced gastritis, arachidonic acid-induced edema, and acetic acid-induced abdominal writhing without displaying toxic profiles in body and organ weight, gastric irritation, or serum parameters. In addition, AQCA suppressed the expression of inflammatory genes such as cyclooxygenase- (COX-) 2 in stomach tissues and lipopolysaccharide- (LPS-) treated RAW264.7 cells. According to reporter gene assay and immunoblotting analyses, AQCA inhibited activation of the nuclear factor- (NF-) κ B and activator protein- (AP-) 1 pathways by suppression of upstream signaling involving interleukin-1 receptor-associated kinase 4 (IRAK1), p38, Src, and spleen tyrosine kinase (Syk). Our data strongly suggest that anthraquinones such as AQCA act as potent anti-inflammatory and antinociceptive components in vivo, thus contributing to the immune regulatory role of fruits and herbs.